Artificial Intelligence Generated Summaries as Digital Scaffolds to Support Learners’ Discourse Level Comprehension of Complex Texts in an Indonesian Senior High School - Mustafa, Rayval; Dharmawan, Yanuarius Yanu (Journal of English Language and Education, 2026)
Discourse-level comprehension is essential for academic literacy, as it enables students to follow arguments across paragraphs, evaluate evidence, and engage in critical reading. In Indonesian EFL classrooms, many senior high school students struggle not only with vocabulary but also with constructing coherent understanding from complex texts. Difficulties in tracking references, connecting ideas, and recognizing rhetorical organization often limit deeper comprehension. This qualitative case study was conducted in a Grade XI class at a private urban senior high school in Bandar Lampung, Indonesia. While classroom activities involved the whole class, eight students were purposively selected for think-aloud protocols and focus group discussions to allow in-depth analysis. Data were collected through observations, think-aloud sessions, discussions, and learning artifacts, and analyzed using reflexive thematic analysis. Findings show that ChatGPT-generated summaries functioned as digital scaffolds, helping students clarify key relationships and verify understanding against the source text, thereby supporting more deliberate and evidence-based reading.